Citizen engagement in healthcare procurement decision-making by healthcare insurers: recent experiences in the Netherlands - Óscar Brito Fernandes; Véronique Bos; Niek Klazinga; Dionne Kringos (BMC, 2022)
Abstract Background In insurance-based healthcare systems, healthcare insurers are interested in engaging citizens in care procurement to contract healthcare services that matter to people. In the Netherlands, an amendment to the Health Insurance Act was set forth in 2021 to formalize and strengthen the engagement of the insured population with healthcare insurers' procurement cycles. This study explores the role of Dutch healthcare insurers in operationalizing citizen engagement in procurement cycles before changes occur linked to the amendment to the Health Insurance Act. Methods A phenomenological qualitative design was employed in two phases: (1) we consulted academics and policy experts on the role of healthcare insurers regarding citizen engagement; (2) we conducted focus groups with representatives of healthcare insurers to understand how citizens' engagement is being operationalized. Transcripts of the interviews with experts and detailed notes of focus group meetings were analysed using a qualitative inductive approach. Selected excerpts were analysed on discourse and content and organized by a coding scheme following a rigorous and accelerated data reduction technique. Results We identified four strategies used by healthcare insurers to operationalize citizen engagement: (1) broadening their population health orientation; (2) developing and improving mechanisms for engaging citizens; (3) strengthening features of data governance for effective use of value-driven data; (4) implementing financial and incentive mechanisms among healthcare providers in support of value-based healthcare. However, regulated market mechanisms and low institutional trust in healthcare insurers undermine their transition from merely funding healthcare towards becoming people-centred value-based healthcare purchasers. Conclusion Dutch healthcare insurers seem to be strengthening the community orientation of their functioning while enhancing the end-to-end experience of the insured. The expected practical effects of the amendment to the Health Insurance Act include broadening the role of the council of insurees in decision-making processes and systematically documenting the efforts set forth by healthcare insurers in engaging citizens. Further research is needed to better understand how the regulated competitive market could be hampering the engagement of citizens in healthcare procurement decision-making and value creation from the citizens' perspective.